2014
DOI: 10.1111/1911-3846.12042
|View full text |Cite
|
Sign up to set email alerts
|

Future Nonaudit Service Fees and Audit Quality

Abstract: Prior to the Sarbanes–Oxley Act of 2002, audit partners experienced economic pressure to grow revenue from the sale of nonaudit services to their audit clients. To an auditor who is highly rewarded for revenue generation and growth, nonaudit services may represent a particularly strengthened economic bond with the client. Prior research shows that, in general, nonaudit service fees received in the current period do not impair audit quality. We examine a different setting. We propose that auditor independence c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
0
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 74 publications
3
65
0
13
Order By: Relevance
“…Further, Lim et al (2013), who do not consider the ratio of institutional investors, found a negative relationship between NAS and audit quality. Causholli et al (2014) found significant evidence that the purchase of future NAS is associated with impaired auditor independence in the current year. We examine whether auditor independence is compromised when audit clients with low performance have an incomeincreasing earnings management incentive.…”
Section: Prior Researchmentioning
confidence: 94%
See 3 more Smart Citations
“…Further, Lim et al (2013), who do not consider the ratio of institutional investors, found a negative relationship between NAS and audit quality. Causholli et al (2014) found significant evidence that the purchase of future NAS is associated with impaired auditor independence in the current year. We examine whether auditor independence is compromised when audit clients with low performance have an incomeincreasing earnings management incentive.…”
Section: Prior Researchmentioning
confidence: 94%
“…Causholli et al. () found significant evidence that the purchase of future NAS is associated with impaired auditor independence in the current year. We examine whether auditor independence is compromised when audit clients with low performance have an income‐increasing earnings management incentive.…”
Section: Prior Research and Nas Regulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…18 There are recent studies that find results suggesting loss of independence. Some of these studies use U.S. data from before SOX (Srinidhi and Gul 2007;Gul, Jaggi, and Krishnan 2007;Krishnan, Su, and Zhang 2011;Omer, Bedard, and Falsetta 2006;Dickins 2008;Causholli, Chambers, and Payne 2014;Bell et al 2015). However, there are others that find evidence of loss of independence using more recent U.S. data (Rice and Weber 2012;Ye 2012), or data from Australia (Ye, Carson, andSimnett 2011), or New Zealand (Wang andHay 2013).…”
Section: Issue 3: Ratio Of Non-audit To Audit Feesmentioning
confidence: 99%